BASELLA ALBA (BASELLACEAE) AND MALE REPRODUCTIVE FUNCTION - Moundipa, P. F.; Monsees, T. K.; Beboy, N. S. E.; Carreau, S.; Nantia, E. A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Hibiscus macranthus and Basella alba leaves are mixed in a remedy given, in western Cameroon, to the new king for some weeks during initiation period to sustain his sexual performance. This plant extracts enhanced blood testosterone level in male rats. They were further studied for androgenic activity since they could be used to alleviate male infertility or to treat androgen deficiency in ageing male. Using rat testis slices, methanol extract of both plants significantly induced testosterone synthesis. In primary Leydig cell cultures of bull and rat, extracts from B. alba significantly enhanced testosterone levels in a dose dependant manner. H. macranthus showed no androgenic activity. Phytochemical screening and HPLC study of B. alba extracts revealed presence of terpenoids, limonoides and coumarins. This extract also modulated aromatase gene activity in Leydig cell cultures. In vivo, methanol extract (1 mg/kg) given to adult male rats significantly increased serum testosterone level after 30 days (p<0.0005). This dose was found to be efficient whereas higher dosages of extract were ineffective. No sign of toxicity was detected in liver and kidney during acute or chronic studies. Acknowledgment: IFS, AUF, Universities of Giessen and Caen (FRG, France)